Can Participation Be Induced? Some Evidence from Developing Countries - Mansuri, Ghazala (World Bank, Washington, DC, 2012)
The World Bank has allocated close to $80 billion towards participatory development projects over the last decade. A comprehensive review of the evidence on the efficacy of the approach conducted by the authors for the forthcoming Policy Research Report, Localizing Development: Does Participation Work?, finds that while participatory projects have been reasonably effective in improving access to basic services, there is far less evidence of their effectiveness in improving household income or in building sustainable participatory institutions at the local level. A key issue is that the institutional culture in development agencies such as the World Bank lacks the flexibility and long-term commitment necessary for effective externally induced participatory development. Induced participation -- driven by large-scale bureaucratically managed processes, is quite different from more organic types of participation endogenously organized by civic groups. It requires a very different approach to development, one that pays close attention to contextual variation and to uncertain trajectories of change. In order to be effective, induced participatory projects need a strong focus on learning-by-doing; on monitoring and evaluation and a willingness to learn from failure. A review of the World Bank's practices in monitoring and evaluation, and of its incentives to learn from failure, reveals that without significant changes, including changes in the incentive structures facing management, the Bank cannot be effective in inducing participation.